Autonomic modulation and skeletal muscle oxygenation with intermittent low-load blood flow restriction knee extension - Andrew R. Garner; Jacob D. Fanno; Ryan McGrath; Jacob Erickson; Kyle J. Hackney (Frontiers in Sports and Active Living)
IntroductionThis investigation determined if an acute bout of low-load knee extension (KE) with intermittent blood flow restriction (BFR) influenced autonomic modulation and skeletal muscle oxygenation (SmO2%).MethodsFourteen physically active males completed three different sessions: one-repetition maximum (1RM), KE with BFR (BFR-KE) at 20% 1RM (cuff pressure=143 ± 13 mmHg), and KE with free blood flow at 20% 1RM (Control-KE). Heart rate variability (HRV) metrics: logarithmically transformed (ln) square root of the mean differences of successive R-R intervals (lnRMSSD), high frequency power (lnHF), and low frequency power (lnLF), as well as SmO2%, and rating of perceived exertion (RPE) were measured. Repeated measures analyses of variance were used to analyze HRV metrics and SmO2%, while a paired t-test was used to analyze RPE. A significance level of P < 0.05 was used for analyses.ResultsFrom baseline to 15 min post-exercise lnRMSSD decreased in both BFR-KE and Control-KE (4.34 ± 0.43–3.75 ± 0.82 ms, P = 0.027). Thereafter, lnRMSSD (+7%), lnHF (+8%), and lnLF (+7%) increased from 15 to 30 min post-exercise in both BFR-KE and Control-KE (P < 0.05). BFR-KE reduced SmO2% in the vastus lateralis compared to Control-KE (36% vs. 53%; P < 0.001). RPE was greater in BFR-KE (7.0 AU) compared to Control-KE (4.5 AU; P < 0.001).ConclusionUnilateral BFR exercise with individualized cuff pressure and intermittent application facilitated greater localized muscular stress and perceptual effort, but there was no influence of vascular occlusion on post-exercise autonomic modulation compared to volume-matched exercise with free blood flow.